Study on genetic divergence analysis of indigenous and exotic lines of linseed (Linum usitatissimum L.) based on morphological and quality traits: GENETIC DIVERGENCE ANALYSIS OF LINSEED BASED ON MORPHOLOGICAL AND QUALITY TRAITS - DEVENDER SHARMA; SATISH PAUL; RANJANA PATIAL (Journal of Oilseeds Research, 2017)
Thirty genotypes of linseed were analysed for sixteen morphological traits to investigate the genetic diversity between and within the genotypes. Field data was initially subjected to analysis of variance. There were highly significant differences among the genotypes for all the traits indicating the presence of adequate variability among the genotypes and the possibility to undertake cluster analysis. The phenotypic divergence and relative importance were estimated bymultivariate analysis. The cluster analysis based on Tocher’s method classified the genotypes into nine major groups. The maximum distance was found between clusters VI and VIII. The genotypes from these clusters can be utilized for the improvement of linseed yield and obtaining good segregants in linseed breeding programs.